Sintering and Crystallization Intensifiers for Production of Ceramic Paving Blocks by Vibropressing Technology - Montayev, Sarsenbek; Omarov, Berik; Ristavletov, Raimberdi; Dosov, Karzhaubay; Montayeva, Nurgul; Dosaliev, Kanat (Periodica Polytechnica Civil Engineering, 2023)
The article presents the results of research on application of sintering and crystallization initiators based on a composition of blast-furnace granulated slag and glass wastes in the ceramic masses for production of ceramic paving blocks by vibro-pressing. The leading role of sintering and crystallization initiators in assuring the strong and dense structure of ceramic pieces was updated. The main laws of changes in physical and mechanical properties of ceramic paving stone samples depending on the amount of sintering and crystallization initiators in the burning temperature range 950–1000 °C have been established. It was determined that the availability of finely dispersed glass powder (fraction less than 0.1 mm) as a component of crystallization sintering initiators contributes to early emergence of liquid phase in the ceramic mass, as softening temperature of glass powder begins already at 720–750 °C. According to the results of X-ray phase and electron microscopic analysis it was determined that crystallization of low-temperature form of ß-wollastonite (CaSiO3) is observed in the samples burnt at the temperature range of 950–1000 °C. It was proved that the availability of ß-wollastonite in the ceramic mass serves as a reinforcing component. It has been established that high strength values are achieved in those compositions where ß-wollastonite crystallization in the burning products is the highest. As a result of scientific and experimental work the feasibility of producing the ceramic paving stones by vibropressing containing sintering and crystallization initiators that meet the requirements of quality, aesthetics, environmental friendliness, resource- and energy-saving was proved.